2018
DOI: 10.1080/0361073x.2018.1477355
|View full text |Cite
|
Sign up to set email alerts
|

Learning facts during aging: the benefits of curiosity

Abstract: These findings show that elderly individuals benefit from the memory-enhancing effects of curiosity. This may lead to the implementation of learning strategies that target and stimulate curiosity in aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 35 publications
8
67
4
Order By: Relevance
“…In young and older adults, curiosity states also enhance memory for incidental face images that are encountered during high-compared to low-curiosity states (Galli et al, 2018;Gruber et al, 2014;Stare et al, 2018). In contrast to our prediction, we did not observe that high-curiosity states increased memory for incidental face images in children and adolescents.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In young and older adults, curiosity states also enhance memory for incidental face images that are encountered during high-compared to low-curiosity states (Galli et al, 2018;Gruber et al, 2014;Stare et al, 2018). In contrast to our prediction, we did not observe that high-curiosity states increased memory for incidental face images in children and adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…To induce curiosity, we used a trivia paradigm in which participants consecutively encoded trivia questions that were associated with varying degrees of curiosity and anticipated the correct answer (see Figure 1). Studies with adults have repeatedly shown that answers to trivia questions associated with high curiosity are better remembered than answers to low-curiosity trivia questions (Fastrich et al, 2018;Galli et al, 2018;Gruber et al, 2014;Kang et al, 2009;Marvin & Shohamy, 2016;McGillivray et al, 2015;Stare, Gruber, Nadel, Ranganath, & Gómez, 2018;Wade & Kidd, 2019). The paradigm consisted of a screening phase in which we selected participant-specific trivia questions for which the answers were unknown and which varied in subjective curiosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The momentary experience of curiosity can be seen as a motivational state that facilitates knowledge acquisition (Silvia & Kashdan, 2009; Gottlieb and Oudeyer, 2018). Consistent with this idea, studies have shown that states of high curiosity enhance long-term memory (Kang et al, 2009; Gruber et al, 2014; McGillivray et al, 2015; Marvin and Shohamy, 2016; Stare et al, 2018; Galli et al, 2018). Furthermore, recent neuroimaging evidence suggests that state curiosity enhances memory via increased activation in the mesolimbic dopaminergic circuit including the hippocampus (Gruber et al, 2014; Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 75%
“…Academically, honesty education expected to prepare students to become positive human beings. Some of the traits that appear in the positive meaning of honesty education are confidence, responsibility, curiosity (Galli et al, 2018), courageous and capable to be honest in all conditions (Syaodih & Handayani, 2017). In addition to raising these traits, honesty predicted to broaden students' insight and make students think genuine and be more creative.…”
Section: Honesty…mentioning
confidence: 99%